The level of anger in patients with substance dependence; its relationship with addiction profile, depression and anxiety level - Ekinci, Suat; Uğur Kural, Hanife; Yalçınay, Merve (Journal of Dependence, 2016)
Objective: The aim of this study is to examine the relationship between anger level, addiction profile and the level of depression and anxiety in patients with substance dependence.Method: The study is conducted with 100 inpatients and outpatients who had the diagnosis of substance use disorders based on DSM-5 criteria in private Balıklı Rum Hospital in Istanbul. The patients that accepted participation to the study and signed informed consent form were included in the study. Sociodemographic Data Form, BussPerry Aggression Questionnaire (BPSÖ), Beck Depression Inventory (BDE), Beck Anxiety Inventory (BAÖ), and Addiction Profile Index (BAPİ) were applied to the participants.Results: There was a positive correlation between BPSÖ, BDA and BDE scores. Similarly, a positive correlation between BPSÖ and BAPİ sub-scales (the impact of substance use on the person’s life, craving) was found.Conclusion: In this study, it was found that there was a relationship between level of anger, depression and anxiety in these patients with the diagnosis of substance dependence. It is revealed that as the level of anger increases, the impact of substance use on the person’s life and the craving increases. For this reason, it is thought that the anger is an important factor which should be considered in the substance dependence treatment process.
Keywords: Substance dependence; addiction profile; anger; anxiety; depression